2019
DOI: 10.2337/dc18-2448
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Trends in Mean HbA1c Are Not Associated With Increasing Rates of Severe Hypoglycemia in Children: A Longitudinal Analysis of Two Contemporary Population-Based Pediatric Type 1 Diabetes Registries From Australia and Germany/Austria Between 1995 and 2016

Abstract: To investigate temporal trends in glycemic control and severe hypoglycemia rates for pediatric patients with type 1 diabetes from 1995 to 2016 by analyzing data from the longitudinal, prospective, population-based German/Austrian (Diabetes Patient History Documentation [DPV]) and Western Australian (Western Australian Children's Diabetes Database [WACDD]) diabetes registries. RESEARCH DESIGN AND METHODS Patients diagnosed with type 1 diabetes aged <15 years were identified from the DPV (N = 59,883) and WACDD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 36 publications
2
29
1
4
Order By: Relevance
“…The frequency of SH was similar in both treatment groups and seemed to be comparable to reported in other studies 33–35 . In recent years, the rates of SH in T1D have been found to follow a decreasing trend, mostly due to new technologies' use 36 . In the present study, CGM‐users experienced a slightly increased rate of SH, which stands in contrast to the similar reports 27,37 .…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of SH was similar in both treatment groups and seemed to be comparable to reported in other studies 33–35 . In recent years, the rates of SH in T1D have been found to follow a decreasing trend, mostly due to new technologies' use 36 . In the present study, CGM‐users experienced a slightly increased rate of SH, which stands in contrast to the similar reports 27,37 .…”
Section: Discussionsupporting
confidence: 89%
“…Two studies found presence of severe hypoglycaemia to be associated with higher BMIz 9,17 . Two multicentre studies investigated the relationship between HbA 1c and severe hypoglycaemia and found no association overall 27,28 . In Denmark the rate of severe hypoglycaemic events has been decreasing during the past decade to <5 events per 100 person years, 14 and we hypothesized that hypoglycaemia would explain some of the association between HbA 1c and BMI, because intensified treatment and fear of hypoglycaemia could lead to increasing intake of carbohydrates when blood glucose is low.…”
Section: Discussionmentioning
confidence: 95%
“…A more recently analysis of the DPV and WACDD cohorts confirmed the decreases in A1C and severe hypoglycemia rate and found similarly low severe hypoglycemia rates in all A1C categories ( Fig. 2 ) ( 31 ). Similarly, in a study ( 34 ) of 1,770 children (<16 years of age) followed between 2000 and 2011, those with A1C <7% did not have higher rates of hypoglycemia compared with children with A1C 8–9%.…”
Section: Evidence Of Decrease In Hypoglycemia Risk—an Evolution Since...mentioning
confidence: 62%
“…The Danish Adult Diabetes Database (DADD) documented an annual decrease of 8.4% in the incidence rate of severe hypoglycemia ( 30 ). An analysis of temporal trends in children diagnosed with T1D <15 years of age from 1995 to 2016 from the longitudinal, prospective, population-based German/Austrian Diabetes Patient History Documentation (Diabetes Patienten Verlaufsdokumenation, DPV) ( N = 59,883) and Western Australian Children's Diabetes Database (WACDD) ( N = 2,595) diabetes registries demonstrated concurrent improvements in A1C and decreasing severe hypoglycemia rates ( 31 ) between 1995 and 2016. The relationship of A1C and severe hypoglycemia has also changed in the 27 years that have elapsed since the DCCT report.…”
Section: Evidence Of Decrease In Hypoglycemia Risk—an Evolution Since...mentioning
confidence: 99%
See 1 more Smart Citation